Simultaneous Polychromatic Immunofluorescent Staining of Tissue Sections and Consecutive Imaging of up to Seven Parameters by Standard Confocal Microscopy. Issue 1 (24th September 2019) - Schmidt, Alfonso J.; Mayer, Johannes U.; Wallace, Paul K.; Ronchese, Franca; Price, Kylie M.
Abstract: Confocal microscopy has been an important imaging tool for life scientists for over 20 years. Early techniques focused on indirect staining processes that involved staining with an unconjugated primary antibody, followed by incubation with a secondary fluorescent antibody that would reveal and amplify the signal of the primary antibody. With more and more directly conjugated fluorescent primary antibodies becoming commercially available, staining with multiple fluorescent primary antibodies is now more frequent. To date, staining with up to three primary antibodies and a nuclear dye is widely practiced. Here, we describe an important improvement to the standard polychromatic immunofluorescent staining protocol that allows the simultaneous detection of seven fluorescent parameters using a standard confocal laser scanning microscope with four laser lines and four photomultiplier tubes. By incorporating recently available tandem dyes that emit in the blue and violet regions of the visible light spectrum (Brilliant Blue and Brilliant Violet), we were able to differentiate several additional fluorochromes simultaneously. Due to the added complexity of 7‐color immunofluorescent imaging, we developed a clear methodology to optimize antibody concentrations and simple guidelines on how to identify and correct non‐specific signals. These are detailed in the following protocol. © 2019 by John Wiley & Sons, Inc. Basic Protocol : 7‐Color immunofluorescent staining protocol using directly conjugated antibodies Support Protocol 1 : Antibody titration protocol Support Protocol 2 : Spillover optimization protocol